PERBEDAAN KUALITAS TIDUR PADA SATPAM DI KOTA PADANG DITINJAU DARI SHIFT KERJA - Velicya, Putri; Rinaldi, Rinaldi (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study aims to determine the differences in sleep quality among security guards (satpam) in Padang City based on their work shift system. The background of this research is rooted in the phenomenon that shift work, particularly night shifts, often disrupts biological rhythms and decreases workers’ sleep quality. Security guards, as a profession requiring high alertness, are especially vulnerable to sleep disturbances due to irregular working hours. This research employed a quantitative approach with a comparative-correlational design. The research subjects consisted of 130 security guards in Padang City selected through purposive sampling. The results revealed a significant difference in sleep quality between day-shift and night-shift security guards, with t = -4.423, df = 128, and p < 0.001. The average sleep quality score of day-shift guards (M = 54; SD = 6.5) was higher than that of night-shift guards (M = 60; SD = 8). Overall, respondents’ sleep quality was categorized as moderate, with the most common issues related to daytime dysfunction and difficulty initiating sleep. This study provides new insights in the field of occupational psychology and industrial health by examining the impact of shift work systems on sleep quality among security guards—a topic that has received limited attention. The findings broaden understanding of circadian rhythm disruption in the context of security work and serve as a foundation for developing work management policies that prioritize the well-being of night-shift employees.